2020
DOI: 10.3390/ijms21113754
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Functional Interrogation of Big Cancer Data Using Drosophila Cancer Models

Abstract: Rapid development of high throughput genome analysis technologies accompanied by significant reduction in costs has led to the accumulation of an incredible amount of data during the last decade. The emergence of big data has had a particularly significant impact in biomedical research by providing unprecedented, systems-level access to many disease states including cancer, and has created promising opportunities as well as new challenges. Arguably, the most significant challenge cancer research currently face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…While this has yielded some clear gains, it is often tough to interpret this big cancer data and to translate it to improved patient care [116]. The way forward will be paved by functional studies in experimental models to reveal the biological significance of the newly identified variants [117]. Here, we sought to determine if tumors with different known initiating mutations share common cell biology in the form of signal pathway activity.…”
Section: Discussionmentioning
confidence: 99%
“…While this has yielded some clear gains, it is often tough to interpret this big cancer data and to translate it to improved patient care [116]. The way forward will be paved by functional studies in experimental models to reveal the biological significance of the newly identified variants [117]. Here, we sought to determine if tumors with different known initiating mutations share common cell biology in the form of signal pathway activity.…”
Section: Discussionmentioning
confidence: 99%
“…It displays high levels of conservation in cancer relevant genes and signalling pathways. It supports easy and fast generations of lines carrying multiples mutated transgenes recapitulating mutational patterns observed in cancer samples as well as genetic modifier screens [10,20]. In addition, genetic tools developed in Drosophila allow to assess how genetically engineered cancer cells interact with their wild type neighbours or cooperate for their survival and expansion [10].…”
Section: Oncogenesis: a Dynamic Process Of Multifactorial Naturementioning
confidence: 99%
“…Through decades of research, we have gained much knowledge on key molecular events and processes involved in the formation of cancer, and much of this knowledge has stemmed from investigations using model organisms, such as the mouse and the vinegar fly, Drosophila melanogaster, in addition to in vitro cell line studies. In this Special Issue, we present a collection of original research papers on various aspects of cancer research utilising human cell lines [7,8], or in vivo using Drosophila as a model system [9,10], as well as reviews highlighting the Drosophila model organism in cancer research [11][12][13][14][15]. Drosophila is a particularly useful model organism for the study of cancer mechanisms, because it has a rapid life cycle and is genetically manipulatable and since cancer genes and signalling pathways are highly conserved between humans and Drosophila, and interactions between tumour cells and surrounding normal cells can be readily examined in Drosophila tissues [6,[16][17][18][19][20].…”
mentioning
confidence: 99%
“…The reviews in this Special Issue highlight the power of using Drosophila as an in vivo model system to study various aspects of cancer research, from its application in the study of the function of specific genes/pathways in cancer [11,15], to understanding particular cellular processes in cancer [13,14], and for functional analyses of cancer Omics data [12]. Sechi et al [15] review the mechanisms of the Golgi phosphoprotein 3 (GOLPH3) oncogene in cancer, covering research on human cancer samples, in vitro cell line analyses and Drosophila in vivo analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation